Welcome to the world, Baby Girl! : a novel - Flagg, Fannie (New York : Ballantine Book, 1998)
Dena Nordstrom, a brainy, beautiful, and ambitious rising star of 1970s television and the pride of the network, is full of promise, her present rich with complications, her past marked by mystery
Keywords: Families -- Missouri -- Fiction; Alcoholics -- New York (State) -- New York -- Fiction; Neighborhood -- Missouri -- Fiction; Mothers and daughters -- Fiction; Roommates -- Fiction; Nineteen seventies -- Fiction; Women television personalities -- Fiction; Missouri -- Fiction; Love stories